2022
DOI: 10.35877/454ri.qems1259
|View full text |Cite
|
Sign up to set email alerts
|

Survival Strategies and Online Marketing in the Time of the COVID-19 Pandemic of Bandung City SME: A Case Study of the Cibaduyut Shoe Center

Abstract: This study aims to describe and analyze survival strategies and online marketing strategies for small shoe businesses during the COVID-19 pandemic in Bandung. This study uses a qualitative method with a case study approach. Data were obtained by interviewing knitting business actors and related parties as key informants. The results showed that the COVID-19 pandemic had a negative impact on small shoe businesses in the shoe center of Bandung city. As a strategic step in the midst of a pandemic, business people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Namun, terdapat beberapa penelitian terkait UMKM di Kota Bandung yang dapat dijadikan acuan untuk melakukan analisis kesenjangan penelitian. (Abdurohim & Ramdan, 2022;Erlangga et al, 2022) ini membahas tentang kendala yang dihadapi UMKM dalam mengembangkannya, termasuk dalam hal sumber daya manusia, keuangan, dan pasar. Studi ini juga menyoroti pentingnya semangat pelaku usaha dalam membuat UMKM terus maju dan mampu bersaing dengan usaha sejenis lainnya.…”
Section: Pendahuluanunclassified
“…Namun, terdapat beberapa penelitian terkait UMKM di Kota Bandung yang dapat dijadikan acuan untuk melakukan analisis kesenjangan penelitian. (Abdurohim & Ramdan, 2022;Erlangga et al, 2022) ini membahas tentang kendala yang dihadapi UMKM dalam mengembangkannya, termasuk dalam hal sumber daya manusia, keuangan, dan pasar. Studi ini juga menyoroti pentingnya semangat pelaku usaha dalam membuat UMKM terus maju dan mampu bersaing dengan usaha sejenis lainnya.…”
Section: Pendahuluanunclassified
“…As the pandemic raged, SMEs' sales fell by 50% in Japan (Fukuda, 2023), 72% in Garowe [Somalia] (Warsame, 2020) and by more than 81% in Calabar [Nigeria] (Ojong-Ejoh et al, 2021). Under such pressure, it became the norm rather than the exception for SMEs to commission websites with payment processing capability in order to salvage their sales (Cheong, 2022;Sonjaya and Ramdan, 2023). According to Almahmood and Tekerek (2022), the added value of digital transformation through e-commerce is its ability to recommend secondary offerings of interest to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that electronic-based marketing strategies can be effective in improving the performance of small businesses. For example, Abdurohim & Ramdan (2022) found that online marketing was crucial for the survival of small businesses during the COVID-19 pandemic. Similarly, Tantri et al (2022) and Isma et al (2020) emphasized the importance of digital marketing strategies in accelerating economic recovery for household businesses.…”
Section: Introductionmentioning
confidence: 99%